2024
DOI: 10.1021/acs.jafc.3c06350
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceutical Potential of Underutilized Tropical Fruits and Their Byproducts: Phenolic Profile, Antioxidant Capacity, and Biological Activity of Jerivá (Syagrus romanzoffiana) and Butiá (Butia catarinensis)

Renan Danielski,
Fereidoon Shahidi

Abstract: Jeriváand butiáare under-valued tropical fruits lacking scientific evidence about their nutraceutical potential. Therefore, they were investigated for their phenolic compound composition and biological activities. Free, esterified, and insolublebound polyphenols were obtained from powdered jeriváand butiápomace and seeds. The total phenolic estimation in seeds (jeriva, 36.45 mg GAE/g; butia, 45.79 mg GAE/g) exceeded pomaces (jeriva, 23.77 mg GAE/g; butia, 18.69 mg GAE/g). Phenolic extracts demonstrated ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
0
0
Order By: Relevance
“…These results are in accordance with the literature [26], which found hydroxy benzoic acid, caffeic acid, syringic acid, coumaric acid, ferulic acid and sinapic acid in jeriva pulp. Throughout the study of polyphenols in jeriva in its soluble, insoluble and esterified portions, a study in the literature [27] reported the presence of several polyphenols such as O-methyl-gallic acid, monogalloyl hexoside, protocatechuic acid, p-hydroxybenzoic acid, ferulic acid, hydroxygallic acid, p-coumaric acid and sinapic-O-glucoside. The total amount of each compound varied according to the extraction method.…”
Section: Resultsmentioning
confidence: 99%
“…These results are in accordance with the literature [26], which found hydroxy benzoic acid, caffeic acid, syringic acid, coumaric acid, ferulic acid and sinapic acid in jeriva pulp. Throughout the study of polyphenols in jeriva in its soluble, insoluble and esterified portions, a study in the literature [27] reported the presence of several polyphenols such as O-methyl-gallic acid, monogalloyl hexoside, protocatechuic acid, p-hydroxybenzoic acid, ferulic acid, hydroxygallic acid, p-coumaric acid and sinapic-O-glucoside. The total amount of each compound varied according to the extraction method.…”
Section: Resultsmentioning
confidence: 99%